Rare Earth Elements Variations in a Hyperacid Crater Lake and Their Relations With Changes in Phreatic Activity, Physico-Chemical Parameters, and Chemical Composition: The Case of Poás Volcano (Costa Rica) - Pappaterra, Sabrina; Inguaggiato, Claudio; Rouwet, Dmitri; Mora-Amador, Raúl; Ramírez-Umaña, Carlos; González, Gino; Brusca, Lorenzo; Peiffer, Loic; Levresse, Gilles; Bellomo, Sergio (Frontiers in Earth Science, 2022)
Decades of geochemical monitoring at active crater lakes worldwide have confirmed that variations in major elements and physico-chemical parameters are useful to detect changes in volcanic activity. However, it is still arduous to identify precursors of single phreatic eruptions. During the unrest phase of 2009–2016, at least 679 phreatic eruptions occurred at the hyperacid and hypersaline crater lake Laguna Caliente of Poás volcano (Costa Rica). In this study, we investigate the temporal variations of Rare Earth Elements (REE) dissolved in Laguna Caliente in order to 1) scrutinize if they can be used as a new geochemical tool to monitor changes of phreatic activity at hyperacid crater lakes and 2) identify the geochemical processes responsible for the variations of REE concentrations in the lake. The total concentration of REE varies from 950 to 2,773 μg kg−1. (La/Pr)N-local rock ratios range from 0.93 to 1.35, and Light REE over Heavy REE (LREE/HREE)N-local rock ratios vary from 0.71 to 0.95. These same parameters vary in relation to significant changes in phreatic activity; in particular, the (La/Pr)N-local rock ratio increases as phreatic activity increases, while that of (LREE/HREE)N-local rock decreases when phreatic activity increases. REE concentrations and their ratios were compared with the variations of major elements and physico-chemical parameters of the lake. Calcium versus (La/Pr)N-local rock and versus (LREE/HREE)N-local rock ratios show different trends compared to the other major elements (Na, K, Mg, Al, Fe, SO4, and Cl). Moreover, a higher loss of Ca (up to 2,835 ppm) in lake water was found with respect to the loss of Al, K, and Na. This loss of Ca is argued to be due to gypsum precipitation, a process corroborated by the mass balance calculation simulating the precipitation of gypsum and the contemporaneous removal of REE from the lake water. The observed relations between REE, changes in phreatic activity, and the parameters commonly used for the monitoring of hyperacid volcanic lakes encourage investigating more on the temporal and cause-effect relationship between REE dynamics and changes in phreatic activity at crater lake-bearing volcanoes.